Analysis of Local Wisdom Values in the Collection of Folk Games of the Malay Community in Moro District, Karimun Regency : Analisis Nilai Kearifan Lokal Pada Kumpulan Permainan Rakyat Masyarakat Melayu Kecamatan Moro Kabupaten Karimun - Helmalia Saputri; Isnaini Leo Shanty; Fabio Testy Ariance Loren (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to analyze the local wisdom values ​​of peace and prosperity found in the collection of folk games of the Malay community in Moro District, Karimun Regency. This study uses a qualitative approach with descriptive research. Data sources were obtained from community leaders and the practice of folk games that are still developing in Moro District. Data collection techniques were conducted through observation, interviews, and documentation. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. Data validity was tested using source triangulation. The results showed that the Malay folk games of Moro District contain local wisdom values ​​of peace, including honesty, politeness, positive thinking, gratitude, commitment, social solidarity, and harmony. Furthermore, these folk games also contain local wisdom values ​​of well-being, including discipline, hard work, mutual cooperation, health, creativity, cultural preservation, and environmental awareness. These values ​​are reflected in the game rules, the implementation process, and the interactions between players. Based on these findings, it can be concluded that folk games serve not only as a form of entertainment, but also as a medium for transmitting local wisdom values ​​that support the creation of peace and community prosperity. Therefore, the preservation of folk games is necessary to ensure that local cultural values ​​are maintained and passed on to future generations.